LEARNING MOTIVATION CHRISTIAN RELIGION EDUCATION STUDENT - erlinda Sitompul (IAKN Tarutung, 2019)
vAbstract, This study aims to determine whether or not the Influence of Parent Communication on theMotivation of Learning Christian Education in Class IX Students of SMP N 1 Pangaribuan, with thehypothesis there is a positive and significant influence between Parent Communication on theMotivation of Learning Christian Religion Education Class IX Students of SMP N 1 Pangaribuan,Tapanuli North of Learning Year 2018/2019.This research uses inferential quantitative descriptive approach, with a population of all IX gradestudents of SMP 1 Pangaribuan, totaling 193 people with a sample are 44 people. Data was collectedby a closed questionnaire of 36 items compiled by the author based on variable indicators accordingto expert theory. The questionnaire trial was conducted on 30 students who were not researchrespondents, and validity and reliability were tested. The results of data analysis indicate that there isa positive and significant influence between Parent Communication on the Motivation of LearningChristian Religion Education in Class IX SMP N 1Pangaribuan North Tapanuli Regency 2018/2019Learning Year with a coefficient of determination (r2 ) = 35.88% and significant influence testobtained F-count F-table (22.97 4.07), meaning that Ho is rejected and Ha is acceptedKeywords: Parent Communication, Motivation to Learn Christian Religion Education